Tablet PC-based competency evaluation for nursing students in three Asian countries: Cross-sectional comparative study. (November 2021) - Yu, Soo-Young; Suh, Eunyoung E.; Kim, Yun-Mi; Nguyen, Thi Anh Phuong; Badamdorj, Oyungoo; Seok, Yoonhee; Jang, Soyoung; Ahn, Jeonghee
Abstract: Aim: This study evaluated a practical competency evaluation for nursing students in three Asian countries using tablet PC-based tests. The need to evaluate practical competencies in a non-face-to-face manner continues to pose challenges in nursing education. Design: This study presents descriptive comparative research on a tablet PC-based evaluation of practical competencies in three countries. Methods: tablet PC-based clinical practice competency evaluation was conducted among nursing college students in Korea, Vietnam and Mongolia. In total, 124 students answered 65 questions for practical competency evaluation and items on its usefulness. Results: Students from Korea had the highest score of nursing competencies (41.6 points; n = 59, SD 6.02), followed by those from Vietnam (26.3 points; n = 30, SD 4.97) and Mongolia (18.4 points; n = 35, SD 5.36). Scores for usability showed an inverse relationship with competency scores. Questions incorporating video showed the lowest proportion of low-discrimination items. Conclusions: This research recognized that using video which provides contextual elements can increase item discrimination. These findings suggest that incorporating video into evaluation items in tablet-PC-based tests is useful for international comparison.